Pengaruh Kompetensi Pengelola Keuangan dan Efektivitas Cash Management System Terhadap Perilaku Fraud dengan Sikap Profesional sebagai Variabel Intervening dalam Tata Kelola Keuangan Pada ITKJEN KKP - Cahyani, Rosari Minar; Prasilowati, Sri Lestari; Mulyanto, Heru (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This study aims to determine the effect of financial manager competence and Cash Management System effectiveness on fraud behavior in the Inspectorate General of the Ministry of Marine Affairs and Fisheries. This study also analyzes the role of professional attitudes as an intervening variable in the relationship between financial manager competence and Cash Management System effectiveness with good financial governance. This study uses Structural Equation Modeling - Partial Least Squares (SEM-PLS) using Smart PLS 3.0 to assess the measurement model (outer model) and structural model (inner model) in the context of research involving financial managers and internal supervisory auditors at the Inspectorate General of Marine Affairs and Fisheries. Evaluation of the measurement model includes validity and reliability tests. Structural model analysis examines the hypothesized relationship between constructs. The findings show that financial manager competence and CMS effectiveness have a positive effect on professional attitudes but do not have a significant effect on fraud behavior directly. Professional attitudes have a negative effect on fraud behavior. Mediation analysis shows that professional attitudes mediate the effect of CMS effectiveness on fraudulent behavior, while competence does not. These results underline the importance of competence and effective CMS in fostering professional attitudes and reducing fraud behavior in the scope of financial managers.